Identification of a transporter Slr0982 involved in ethanol tolerance in cyanobacterium Synechocystis sp. PCC 6803 - Zhang, Yanan; Niu, Xiangfeng; Shi, Mengliang; Pei, Guangsheng; Zhang, Xiaoqing; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2015)
Cyanobacteria have been engineered to produce ethanol through recent synthetic biology efforts. However, one major challenge to the cyanobacterial systems for high-efficiency ethanol production is their low tolerance to the ethanol toxicity. With a major goal to identify novel transporters involved in ethanol tolerance, we constructed gene knockout mutants for 58 transporter-encoding genes of Synechocystis sp. PCC 6803 and screened their tolerance change under ethanol stress. The efforts allowed discovery of a mutant of slr0982 gene encoding an ATP-binding cassette transporter which grew poorly in BG11 medium supplemented with 1.5% (v/v) ethanol when compared with the wild type, and the growth loss could be recovered by complementing slr0982 in the ∆slr0982 mutant, suggesting that slr0982 is involved in ethanol tolerance in Synechocystis. To decipher the tolerance mechanism involved, a comparative metabolomic and network-based analysis of the wild type and the ethanol-sensitive ∆slr0982 mutant was performed. The analysis allowed the identification of four metabolic modules related to slr0982 deletion in the ∆slr0982 mutant, among which metabolites like sucrose and L-pyroglutamic acid which might be involved in ethanol tolerance, were found important for slr0982 deletion in the ∆slr0982 mutant. This study reports on the first transporter related to ethanol tolerance in Synechocystis, which could be a useful target for further tolerance engineering. In addition, metabolomic and network analysis provides important findings for better understanding of the tolerance mechanism to ethanol stress in Synechocystis.